100 Lyrics : Gulzar - Gulzar; Shekhar, Sunjoy (Trans.) (Gurugram Penguin Books, 2012)
From 'Mora gora ang lai le', his first film lyric written for Bimal Roy's Bandini in 1963, to the Oscar-winning 'Jai ho' from Slumdog Millionaire, Gulzar has brought a rare poetic sensibility to popular Hindi film music over a five-decade-long career. His sophisticated insights into psychological complexities, his ability to capture the essence of nature's sounds and spoken dialects in written words, and above all his inimitable - and often surprising - imagery have entertained his legions of fans over successive generations. It features anecdotes about the composition of the lyrics as well as sketches...
Keywords: poetry